Pest categorisation of Oligonychus mangiferus - EFSA Panel on Plant Health (PLH) (Wiley, 2021)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of the mango red spider mite, Oligonychus mangiferus (Rahman and Sapra, 1940) (Acari: Prostigmata: Tetranychidae), for the territory of the EU. This species is not included in the EU Commission Implementing Regulation 2019/2072. The polyphagous mite feeds on more than 50 host plants including tropical fruits such as mangoes and avocados and temperate fruits such as pears, peaches, pomegranates and grapes. It occurs in Africa, Asia, Oceania and South America. O. mangiferus is multivoltine and can develop throughout the year as long as temperatures are above 12°C. The species produces dense webs on the above‐ground parts of their host plants, where all stages of development (egg, larva, nymph and adult) can be found. This species is considered a pest of mango, grapevine, lychee and pomegranate, mostly in areas with hotter climates than those occurring in the EU. Potential entry pathways for O. mangiferus include plants for planting with foliage, fruit and cut flowers. Plants for planting of a few hosts (i.e. Pinus, Prunus, Pyrus, Rosa, Vitis and Arecaceae) are banned from entering into the EU from countries where O. mangiferus is known to occur and can be considered as closed entry pathways. However, other plants for planting, as well as the fruit and the cut flowers pathways remain open. There are no EU records of interception. Should O. mangiferus enter the EU, the ample availability of hosts and the climatic conditions in the EU would most probably allow this species to successfully establish and spread, at least in southern MSs, where economic impact in different fruit production (e.g. pomegranate, mango and grape) is anticipated. O. mangiferus satisfies the criteria that are within the remit of EFSA to assess for this species to be regarded as a potential Union quarantine pest.